The EUSO-Balloon pathfinder - Adams, J. H. (2015)
EUSO-Balloon is a pathfinder for JEM-EUSO, the Extreme UniverseSpace Observatory which is to be hosted on-board the International Space Station. As JEM-EUSO is designed to observe Ultra-High Energy Cosmic Rays (UHECR)-induced Extensive Air Showers (EAS) by detecting their ultraviolet light tracks "from above", EUSO-Balloon is a nadir-pointing UV telescope too. With its Fresnel Optics and Photo-Detector Module, the instrument monitors a 50 km 2 ground surface area in a wavelength band of 290-430 nm, collecting series of images at a rate of 400,000 frames/sec. The objectives of the balloon demonstrator are threefold: a) perform a full end-to-end test of a JEM-EUSO prototype consisting of all the mainsubsystems of the space experiment, b) measure the effective terrestrial UV background, with a spatial and temporal resolution relevant for JEM-EUSO. c) detect tracks of ultraviolet light from near space for the first time. The latter is a milestone in the development of UHECR science, paving the way for any future space-based UHECR observatory. On August 25, 2014, EUSO-Balloon was launched from Timmins Stratospheric Balloon Base (Ontario, Canada) by the balloon division of the French Space Agency CNES. From a float altitude of 38 km, the instrument operated during the entire astronomical night, observing UV-light from a variety of ground-covers and from hundreds of simulated EASs, produced by flashers and a laser during a two-hour helicopter under-flight.